Rilmenidine treatment in patients with mild to moderate arterial hypertension and metabolic syndrome - S. S. Yakushin; N. I. Ivankova; N. S. Sazonova; N. V. Vilesova; G. O. Ivanova (Российский кардиологический журнал, 2004)
Efficacy, tolerability and cardioprotective properties of rilmenidine were examined in patients with mild to moderate arterial hypertension (AH). The trial involved 51 hypertensive subjects, mean age 57,7+2,5 years. After wash-out period, rilmenidine was administered in the daily dose of 1-2 mg. At baseline and 12 weeks later, blood pressure (BP) and heart rate (HR) dynamics was assessed by the data from 24-hour BP monitoring (BPM), echocardiography, and biochemical blood assay. Good clinical efficacy and tolerability of albarel was observed, without disturbances of lipid, carbohydrate, electrolyte, purin metabolism, functional status of liver and kidneys. Rilmenidine treatment was also associated with EchoCG parameters improvement. Rilmenidine was effective and safe in arterial hypertension treatment, demonstrating cardioprotective properties as well.